Front Cover: Cytoplasmic delivery of quantum dots via microelectrophoresis technique. Issue 11 (4th June 2021) - Han, Mengke; Zhao, Jiangbo; Fabian, Joseph Mahandas; Evans, Samuel; Mustafa, Sanam; Ruan, Yinlan; Wiederman, Steven; Ebendorff‐Heidepriem, Heike
Abstract : DOI: 10.1002/elps.202000388 The cover picture shows monodispersed quantum dots with negative surface charges being injected through a fine‐tipped glass micropipette into the cytoplasm of a live human embryonic kidney cell (roughly 20–30 μm in length) via small electrical current (−0.2 nA). The average hydrodynamic diameter of quantum dots is 13.2–35.0 nm. The inner tip diameter of micropipettes is approximately 200 nm. This technique, so called microelectrophoresis, is promising as a simple and general strategy for the delivery of a variety of nanoparticles into the intracellular environment.